On multiplication lattice modules - (:unkn) unknown (HACETTEPE UNIV, FAC SCI, 2014)
In this paper we study multiplication lattice modules. Next we characterize hollow lattices modules. We also establish maximal elements in multiplication lattices modules. In [16], we introduced the concept of a multiplication lattice L-module and we characterized it by principal elements. In this paper, we continue study on multiplication lattice L-module.
Keywords: Multiplicative lattices; Lattices modules; prime elements; PRIME ELEMENTS